2006
DOI: 10.1038/sj.npp.1301212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Tryptophan Depletion on Mood and Facial Emotion Perception Related Brain Activation and Performance in Healthy Women with and without a Family History of Depression

Abstract: The present study examined the effects of acute tryptophan (Trp) depletion (ATD), a well-recognized method to lower central serotonin (5-HT) metabolism, on brain activation during a facial emotion perception task. Brain activation was measured using fMRI, and healthy female volunteers with a positive family history of unipolar depression (FH + ) were compared to healthy female volunteers without such a history (FHÀ). Participants viewed two morphed faces and were instructed to choose between the faces based ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 36 publications
12
78
1
Order By: Relevance
“…Furthermore, the activation of the amygdala significantly increased in the normal group with a family history of depression as compared to the other group. [17] The activation of the putamen and insula was significantly lower in the normal group with a family history of depression than in the other group without a family history of depression in a reward expected situation, whereas the activation of the anterior cingulate cortex was significantly higher in the normal group with a family history of depression than in the other group in a punishment expected situation. [18] The aforementioned results are expected to explain some of the hereditary and risky aspects of complex depression.…”
Section: Prediction Of the Risk Factors On Depressionmentioning
confidence: 80%
“…Furthermore, the activation of the amygdala significantly increased in the normal group with a family history of depression as compared to the other group. [17] The activation of the putamen and insula was significantly lower in the normal group with a family history of depression than in the other group without a family history of depression in a reward expected situation, whereas the activation of the anterior cingulate cortex was significantly higher in the normal group with a family history of depression than in the other group in a punishment expected situation. [18] The aforementioned results are expected to explain some of the hereditary and risky aspects of complex depression.…”
Section: Prediction Of the Risk Factors On Depressionmentioning
confidence: 80%
“…Second, the (serial) reversal-learning tasks in studies with humans, particularly the one employed here, do not load on inhibitory control as much as do the paradigms used in studies with nonhuman primates, for whom reinforcement is more salient and thus, habit formation more pronounced (Clarke et al, 2007). Finally, neuroimaging studies with human volunteers have shown particularly pronounced effects of ATD on the (dorso)medial PFC during cognitive performance (Cools et al, 2005a;Evers et al, 2005Evers et al, , 2006aTalbot and Cooper, 2006;Van der Veen et al, 2007). Conversely, the disinhibitory effects resulted from selective 5-HT depletion in the OFC (Clarke et al, 2004(Clarke et al, , 2005(Clarke et al, , 2007.…”
Section: Discussionmentioning
confidence: 95%
“…Studies with healthy human volunteers have demonstrated potentiated processing of punishment-related signals after dietary depletion of the 5-HT precursor tryptophan (TRP; acute tryptophan depletion, ATD), particularly in vulnerable individuals. For example, ATD enhanced the amygdala response to fearful faces (Cools et al, 2005b; Van der Veen et al, 2007), decreased the impact of positively valenced words (Murphy et al, 2002), and increased the impact of negatively valenced emotional words in Stroop-like tasks (Evers et al, 2006a). In addition, ATD potentiated neural activity during negative feedback in a probabilistic reversal-learning task (Evers et al, 2005), which was also sensitive to acute administration of the selective serotonin reuptake inhibitor citalopram (Chamberlain et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Previous research showed interactions between the 5-HTTLPR genotype and the effect of ATD on motivational behavior and passive avoidance [45,46]. In addition, our own group confirmed the influence of biological factors on the effect of ATD [89]. The effect of ATD on facial recognition was studied in healthy women with and without a family history of depression.…”
Section: The Influence Of Biological and Psychological Factorsmentioning
confidence: 61%